Topographic bone thickness maps to evaluate the intuitive placement of titanium miniplates for nasal prostheses - Plath, Karim; Jung, Alexander; Wimmer, Wilhelm; Engel, Michael; Möhlenbruch, Markus Alfred; Federspil, Philippe A. (International journal of oral and maxillofacial surgery, 2020)
The aim of this study was to evaluate the intuitive placement of titanium miniplates. The hypothesis was that virtual planning can improve miniplate placement. Twenty patients were included in the study. These patients were fitted with 21 titanium miniplates (16 y-plates, three t-plates, and two u-plates) to retain nasal prostheses between 2005 and 2017. Colour-coded topographic bone thickness maps (TBTMs) were created in fused pre- and postoperative computed tomography. Implants were virtually transposed at the position of highest bone thickness. The bone thickness index (BTI) was calculated as the sum of points assigned at each screw (1 point per millimetre up to 4 mm, and 5 points for greater values) divided by the number of screws. One plate broke after 2.8 years, thus plate survival after 5 years was 91% using the Kaplan-Meier method. The BTI for all 21 plates increased from 3.4 to 4.1 points using virtual transposition (P<0.001). No significant changes were observed in t- and u-plates, but the median BTI increased from 3.1 to 4.1 points (P<0.0005) in 16 y-plates. The change was substantial (≥0.5 points) in 9/16 y-plates. Therefore, the hypothesis that virtual planning improves implant placement was accepted.
Gesehen am 14.10.2020